An annotated checklist of the chondrichthyans of South Africa - Ebert, David A.; Wintner, Sabine P.; Kyne, Peter M. (Zootaxa, 2021)
An annotated checklist of chondrichthyan fishes (sharks, batoids, and chimaeras) occurring in South African waters is presented. The checklist is the result of decades of research and on-going systematic revisions of the regional fauna. The chondrichthyan fauna of South Africa is one of the richest in the world with 191 species, comprising 50 families and 103 genera. It consists of 30 families, 64 genera, and 111 species of sharks; 17 families, 36 genera, and 72 species of batoids; and, 3 families, 5 genera, and 8 species of chimaeras. The most species-rich shark families are the whaler sharks Carcharhinidae with 20 species followed by the deepwater catsharks Pentanchidae with 13 species. The most species-rich batoid families are the hardnose stakes Rajidae with at least 21 species followed by the stingrays Dasyatidae with 13 species. This monograph represents the first detailed annotated checklist of chondrichthyans from South Africa in over 30 years.